2019
DOI: 10.1099/mgen.0.000289
|View full text |Cite
|
Sign up to set email alerts
|

Genetic affinities of an eradicated European Plasmodium falciparum strain

Abstract: Malaria was present in most of Europe until the second half of the 20th century, when it was eradicated through a combination of increased surveillance and mosquito control strategies, together with cross-border and political collaboration. Despite the severe burden of malaria on human populations, it remains contentious how the disease arrived and spread in Europe. Here, we report a partial Plasmodium falciparum nuclear genome derived from a set of antique medical slides stained with the blood of malaria-infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 46 publications
2
12
0
Order By: Relevance
“…Over the last decade, ancient-pathogen genomics has made great progress by borrowing technological advances originally developed for the study of human ancient DNA (17, 18). Although most microbial data has been secondarily generated from the sequencing of ancient human bones or teeth (1821) other, rare samples, such as preserved tissues (22, 23) or microscope slides from antique medical collections have been analysed (17, 24). We are aware of no previous attempt to leverage ancient DNA technology to diagnose infections in historical characters, despite previous sequencing of remains from other prominent historical figures such as King Richard III and the putative blood of Louis XVI (25, 26).…”
Section: Discussionmentioning
confidence: 99%
“…Over the last decade, ancient-pathogen genomics has made great progress by borrowing technological advances originally developed for the study of human ancient DNA (17, 18). Although most microbial data has been secondarily generated from the sequencing of ancient human bones or teeth (1821) other, rare samples, such as preserved tissues (22, 23) or microscope slides from antique medical collections have been analysed (17, 24). We are aware of no previous attempt to leverage ancient DNA technology to diagnose infections in historical characters, despite previous sequencing of remains from other prominent historical figures such as King Richard III and the putative blood of Louis XVI (25, 26).…”
Section: Discussionmentioning
confidence: 99%
“…Presently approximately 80 non–synonymous pf MRP1 SNPs are known ( Figure 1 ), the majority of them present at very low (<0.1%) global frequencies (data mainly provided through the MalariaGen project). The global distribution of SNPs is variable, with some positions being widely distributed, like the frequently linked Y191H/A437S ( Mu et al, 2003 ; Ursing et al, 2006 ; Pirahmadi et al, 2013 ), as well as I876V ( Dahlstrom et al, 2009 ; Gupta et al, 2014 ; Zhao et al, 2019 ; Al-Ruhmi et al, 2020 ), which seems to have been circulating at least since pre-chloroquine times ( de Dios et al, 2019 ). Others are clustered in some regions, like the 1466 position, frequent in East Africa ( Dahlstrom et al, 2009 ; 2009a ), but rare in the Western coast ( Otienoburu et al, 2016 ; Jovel et al, 2017 ), and found absent in studies in Asia ( Veiga et al, 2011 ; Gupta et al, 2014 ; Phompradit et al, 2014 ) as well as in the Americas ( Dahlstrom et al, 2009 ).…”
Section: Sequence Diversitymentioning
confidence: 99%
“…These parasites are transmitted into the susceptible human host through the bite of an infected female Anopheles mosquito during a blood meal. Plasmodium falciparum is responsible for the majority of malaria cases and deaths occurring in sub-Saharan Africa [3] where about 99.7% of all malaria morbidity and mortality are attributed to the specie with a disproportionate number of deaths in children under the ages of five [4].…”
Section: Introductionmentioning
confidence: 99%